2015
DOI: 10.1177/0284185114550702
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, multicenter study of a double stent system for palliative treatment of malignant extrahepatic biliary obstructions

Abstract: Percutaneous treatment of malignant extrahepatic biliary obstruction using a double stent safely and effectively achieves internal biliary drainage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…3,8,10,13,25,31 Similarly, the overall survival time of 150 days seen in the current study was similar to the 132e394 days reported previously. 3,8,10,13,31 The study has some inherent limitations. First, data collection was performed retrospectively and this may affect the reliability of the evaluation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…3,8,10,13,25,31 Similarly, the overall survival time of 150 days seen in the current study was similar to the 132e394 days reported previously. 3,8,10,13,31 The study has some inherent limitations. First, data collection was performed retrospectively and this may affect the reliability of the evaluation.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are in accordance with the results of previous studies, which showed a technical success rate of 99.4e100%, an overall complication rate of 6.9e23.4%, and a successful internal drainage rate of 79.7e100%. 3,8,10,13,25,31 In addition, we saw a median stent patency duration of 117 days, which is similar to previous reports of 114e317 days. 3,8,10,13,25,31 Similarly, the overall survival time of 150 days seen in the current study was similar to the 132e394 days reported previously.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Various methods of preventing stent migration have been described [10,11,26]. In our study, no stent migration occurred, and we assume that our partially covered stent design with both bare ends (CBD section and long limb of the main piece, and contralateral limb) may resist migration of the stent.…”
Section: Discussionmentioning
confidence: 60%
“…The use of covered stents in the biliary system was initially developed to address the issue of tumor ingrowth. A variety of covering materials have been manufactured and tested to prevent tumor ingrowth and to avoid the need for re-intervention ( 5 6 7 8 9 10 11 12 13 14 15 ). In last 12 years, polytetrafluoroethylene (PTFE)-covered stents have been demonstrated as an effective treatment method ( 9 10 11 12 13 14 15 ), with the PTFE material serving as an effective barrier to prevent tumor ingrowth.…”
Section: Introductionmentioning
confidence: 99%